Exploring the challenges and opportunities of big data in SMEs: A bibliometric analysis - Bernardino, Maria Francisca Silva Carvalho (2023)
The aim of this thesis is to investigate the challenges and opportunities associated with the implementation of big data in small and medium-sized enterprises. The main findings of this study, based on a bibliometric analysis using Elsevier Scopus as a search engine and Vos viewer to analyze the results, demonstrates that big data analytics enables SMEs to improve financial performance and operational efficiency, become more innovative and able to make more informed decisions. Thus, enabling SMEs to achieve stable growth and gain competitiveness in the market. This study results from the synthesis of existing literature, which provides useful information and practical recommendations for SMEs, policy makers and researchers. The results help to understand the decisive factors of big data adoption in SMEs and paves the way for future research in this area.